Impact of Hemodialysis on Dyspnea and Lung Function in End Stage Kidney Disease Patients - Palamidas, Anastasios F. (Hindawi Publishing Corporation, 2014)
Background. Respiratory symptoms are usually underestimated in patients with chronic kidney disease undergoing maintenance hemodialysis. Therefore, we set out to investigate the prevalence of patients chronic dyspnea and the relationship of the symptom to lung function indices. Methods. Twenty-five clinically stable hemodialysis patients were included. The mMRC dyspnea scale was applied before and after hemodialysis. Spirometry, single breath nitrogen test, arterial blood gases, static maximum inspiratory (P (imax⁡)) and expiratory (P (emax⁡)) muscle pressures, and mouth occlusion pressure (P (0.1)) were also measured. Results. Despite normal spirometry, all patients (100%) reported mild to moderate degree of chronic dyspnea pre which was reduced after hemodialysis. The sole predictor of (Δ) mMRC was the (Δ) P (0.1) (r = 0.71, P < 0.001). The P (imax⁡) was reduced before and correlated with the duration of hemodialysis (r = 0.614, P < 0.001), whilst after the session it was significantly increased (P < 0.001). Finally (Δ) weight was correlated with the (Δ) P (imax⁡)  %pred (r = 0.533, P = 0,006) and with the (Δ) CV (%pred) (r = 0.65, P < 0.001). Conclusion. We conclude that dyspnea is the major symptom among the CKD patients that improves after hemodialysis. The neuromechanical dissociation observed probably is one of the major pathophysiologic mechanisms of dyspnea.